Hubungan Keharmonisan Keluarga dengan Perilaku Bullying pada Remaja - Itsna Miftahurrohmah; Neni Noviza; Lena Marianti (Journal of Society Counseling, 2025)
This research is entitled "The Relationship between Family Harmony and Bullying Behavior in Adolescents at Rumah Tahfidz Pinggiran (RTP) Palembang". The PPPA (Empowerment, Child Protection, and Population Control) Office, when conducting socialization about bullying at the suburban tahfidz house, found that some children were bullied to the point of being afraid to recite. As a religious educational institution, the tahfidz house should uphold moral and ethical values. However, if bullying occurs and affects family harmony, this can have an impact on the attitude and behavior of students or teenagers in the tahfidz house. The researcher's goal was to find out the relationship between family harmony and bullying behavior in adolescents in Palembang suburban Tahfidz houses (RTP). In this study, a quantitative method of correlation/relationship is used. This study uses Purposive sampling, which is a sampling technique based on certain criteria. Sampling of researchers, this refers to Suharsimi Arikunto, if the population is less than 100 people, then it should be taken from the entire population. If the population is large or more than 100, then it can be taken as 5-15% or, 20-25%, or more. The criteria in this study are adolescents aged 12-15 years who are in Palembang suburban Tahfidz houses (RTP). The sample was taken 20% of the total population, namely 165 people, so the sample in this study was 33 people. The data collection technique uses questionnaires and documentation. Before conducting the instrument test, namely the validity and reliability test. The data analysis technique is Pearson Product-Moment correlation. The results of this study are that there is a significant negative correlation between family harmony and bullying behavior in adolescents in Palembang suburban tahfidz houses (RTP), this can be seen from the acquisition of Pearson correlation obtained r= -0.611 with a significance of 0.000 with a significance level (< 0.05), so that the hypothesis that states that there is a sig correlation negative between family harmony and bullying behavior in adolescents at the Palembang periphery tahfidz house (RTP) was accepted.